2000
DOI: 10.1046/j.1432-1327.2000.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the haem–nicotinate interaction in leghaemoglobin

Abstract: A strategic assessment of the contributions of two active-site hydrogen bonds in the binding of nicotinate to recombinant ferric soybean leghaemoglobin a (rLb) was carried out by mutagenic replacement of the hydrogenbonding residues (H61A and Y30A variants) and by complementary chemical substitution of the carboxylate functionality on the nicotinate ligand. Dissociation constants, K d (pH 5.5, m 0.10 m, 25.0^0.1 8C), for binding of nicotinate to ferric rLb, H61A and Y30A were 1.4^0.3 mm, 19^1 mm and 11^1 mm, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Similarly, using disodium 2,6-dichlorophenolindophenol ( E m = 217 mV, Table S1), the reduction potential of cytochrome c was determined as E m = 261 mV ± 2 mV (data not shown), which compared well to literature values [34–39]. We find that the methodology is faster than other mediated [23,4042] methods and more convenient than direct electrochemistry methods [16], because electrons are exchanged in bulk solution instead of via mediated electron transfer between the protein and thin-layer electrode, which means that equilibria are reached more quickly (and avoids very long equilibration times), and the process is not vulnerable to surface contamination. Since the method is based on equilibration, in principle it can be used at any pH or temperature at which the proteins involved are stable and the corresponding equilibration reactions occur at reasonable rates.…”
Section: Resultssupporting
confidence: 82%
“…Similarly, using disodium 2,6-dichlorophenolindophenol ( E m = 217 mV, Table S1), the reduction potential of cytochrome c was determined as E m = 261 mV ± 2 mV (data not shown), which compared well to literature values [34–39]. We find that the methodology is faster than other mediated [23,4042] methods and more convenient than direct electrochemistry methods [16], because electrons are exchanged in bulk solution instead of via mediated electron transfer between the protein and thin-layer electrode, which means that equilibria are reached more quickly (and avoids very long equilibration times), and the process is not vulnerable to surface contamination. Since the method is based on equilibration, in principle it can be used at any pH or temperature at which the proteins involved are stable and the corresponding equilibration reactions occur at reasonable rates.…”
Section: Resultssupporting
confidence: 82%
“…Ferrous proteins were generated by stoichiometric titration of the ferric enzyme with sodium dithionite. Equilibrium binding constants, K D , were determined in accordance with previously reported procedures .…”
Section: Methodsmentioning
confidence: 99%
“…The crystal structures of nicotinic acid (Wright & King, 1953;Kutoglu & Scheringer, 1983), dinicotinic acid (Takusagawa et al, 1973), isonicotinic acid (Takusagawa & Shimada, 1976), isonicotinic acid hydrazide (Bhat et al, 1974), nicotinium tetrachlorocuprate(II) (Choi et al, 2002), 2-aminonicotinic acid (Dobson & Gerkin, 1997), 6-aminonicotinic acid hydrochloride (Giantsidis & Turnbull, 2000), nicotinic acid chloride hydrochloride (Nä ttinen & Rissanen, 2003), 3,5-dinitrobenzoic acid nicotinic acid (Zhu & Zheng, 2004), 2-(methylsulfanyl)nicotinic acid (Basavoju et al, 2005), nicotinamide (Wright & King, 1954), 1-methylnicotinamide iodide, chloride and picrate (Freeman & Bugg, 1974), and dinicotinamidium squarate (Bulut et al, 2003) have been reported previously. The crystal structure of nicotinic acid complexed with the protein leghaemoglobin (Ellis et al, 1997) and the haemnicotinate interaction in leghaemoglobin (Patel et al, 2000) were also studied. As part of our investigations of nicotinic acid complexes with inorganic acids, nicotinic acid was treated with sulfuric acid, and the crystal structure of the resulting salt is reported here.…”
Section: Commentmentioning
confidence: 99%